Reduction of Feedback Availability Limits Self-Control Effects - von Lindern, Aaron D.; Fairbrother, Jeffrey T. (Frontiers in Sports and Active Living, 2022)
A growing body of research has demonstrated that providing learners with self-control over aspects of the learning environment facilitates the learning of a motor skill (for reviews see Fairbrother, 2019; Wulf, 2007). In applied group settings, however, the provision of feedback is at times constrained by factors such as instructor availability. The purpose of the present study, therefore, was to examine how learners ostensibly provided self-control over feedback responded when the actual availability of feedback was constrained by a predetermined schedule of a virtual coach’s availability to provide feedback. Participants were divided into four feedback groups and completed 72 practice trials of a sequential key-pressing task, with three different goal movement times (900 ms, 1200 ms, 1500 ms). The KR100 group received knowledge of results (KR) after every practice trial. The KR50 group received KR on an evenly distributed quasi-randomly determined schedule after 50% of the trials. The SC group had the opportunity to request KR after every trial, but KR was only available for 50% of practice trials according to the same schedule used for the KR50 group. The YK (i.e., yoked) group received KR according to the schedule of KR received by counterparts in the SC group. Approximately 24 hr after acquisition, each participant returned to complete retention and transfer tests. The retention test consisted of 15 no-KR trials of the acquisition tasks (five trials for each goal time – 900 ms, 1200 ms, 1500 ms). The transfer test consisted of 15 no-KR trials with new time goals (1300 ms, 1600 ms, 1900 ms). Results revealed a significantly lower absolute constant error (ACE) score for the SC group during transfer (p < .05), suggesting that SC effects can occur in a reduced feedback availability environment. Other measures, however, failed to show significant advantages for the SC group during any phase of the study suggesting that effects were not as robust as previous research has indicated. The results also provided some indication that perceived scarcity might have played a role in elevating the number of feedback requests in response to the reduced autonomy environment.